DEMOKRASI KAUM SANTRI DALAM PANDANGAN ISLAM (Mendudukkan Konsep Demokrasi dan Ittiba>’ Kiai) - Ansori, Ibnu Hajar; Nasikah, Roudlatun (Jurnal Dakwah, 2019)
Kiai is the central figure in Indonesia's political world. The involvement of kiai is the implementation of loving motherland concept, as well as manifestation of exemplary to Prophet who not only as a religious leader, but also a statesman who leads the fight for peace, justice and prosperity. That role can be seen for example from the notice issued by the kiai in Presidential election 2019. The masyayikh (kiai) appeals the students and the extended family of the pesantren to not abstain and directs them to choose certain president candidate in the 2019 election. For santri, emulate and follow (ittiba>’) or that notice is a inevitability even though it seems contrary with the concept of democracy which adheres to the freedom of speech principle. Through this article, santri tradition in democracy will be analyzed descriptively analytically with the al-Qur'an and hadith approach. From the results of the study, it is found that that the observance of santri to Kiai is the actualization of the meaning of QS. al-Kahfi: 66 about the story of the Prophet Khidir and Musa, which illustrates the students obedience to the teacher. Beside, the santri democratic tradition concept can be called taadub democracy which is based on the santri manners or attitudes toward his teacher. Regarding to how the decision made, the kiai opens the opportunity and let the santri to decide, even though it will be responded by the santri with the principle of sami’na> wa at}a’na. If forced to be different, then they must pay attention to the relationship ethics between students and kiai, so it will not become obstacles to the benefit and blessing of knowledge.